2008
DOI: 10.1111/j.1471-0307.2008.00365.x
|View full text |Cite
|
Sign up to set email alerts
|

Viability of probiotic micro‐organisms (Lactobacillus casei Shirota and Bifidobacterium animalis subspp. lactis) in a milk‐based dessert with cranberry sauce

Abstract: The objective of this study was to evaluate the survival of two probiotic micro‐organisms, Lactobacillus casei Shirota and Bifidobacterium animalis subspp. lactis, in a milk‐based dessert (2.7% fat) with cranberry sauce added. B. lactis had a final concentration of 1.99 × 106 cfu/g after 21 days of study, with a logarithmic decrease of 8.87%. On other hand, L. casei Shirota had a final concentration of 2.05 × 107 cfu/g at the end of the same period, a logarithmic decrease of 8.41%. Statistical analysis showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 15 publications
(23 reference statements)
1
5
0
1
Order By: Relevance
“…The lowest production of lactic acid at the 21st day was obtained in puddings with L. acidophilus 1748 (around 5000 mg/kg), equivalent to 50% of the content produced by L. rhamnosus GG. The study results regarding the use of probiotics in co-culture were quite similar to those observed by Magariños et al (2008) for milk-based desserts containing B. animalis Bb12 and L. casei Shirota, with initial pH of 6.8, later reduced to 6.52 at the 21st storage day at 5 °C, as well. The authors also observed that the use of L. acidophilus La-5 in a co-culture with B. animalis Bb12 resulted in the lowest acetoin (33.6 mg/kg) and ethanol (3.5 mg/kg) contents.…”
Section: General Effects Of the Food Matrix On Physicochemical Characsupporting
confidence: 83%
See 1 more Smart Citation
“…The lowest production of lactic acid at the 21st day was obtained in puddings with L. acidophilus 1748 (around 5000 mg/kg), equivalent to 50% of the content produced by L. rhamnosus GG. The study results regarding the use of probiotics in co-culture were quite similar to those observed by Magariños et al (2008) for milk-based desserts containing B. animalis Bb12 and L. casei Shirota, with initial pH of 6.8, later reduced to 6.52 at the 21st storage day at 5 °C, as well. The authors also observed that the use of L. acidophilus La-5 in a co-culture with B. animalis Bb12 resulted in the lowest acetoin (33.6 mg/kg) and ethanol (3.5 mg/kg) contents.…”
Section: General Effects Of the Food Matrix On Physicochemical Characsupporting
confidence: 83%
“…Different results were obtained by Magariños et al (2008) regarding probiotic milk-based desserts (containing B. animalis Bb12 and L. casei Shirota) served with cranberry sauce (added soon before the sensory evaluation was conducted). The authors reported consecutive significant acceptability reductions (p < 0.05), after 14 and 21 days of storage.…”
Section: Influence Of Probiotic Cultures and Prebiotic Ingredients Onmentioning
confidence: 99%
“…The authors found satisfactory population of L. paracasei in two formulations, which remained above 6 log CFU/g during 28 days of storage at 5 °C. Magariños et al (2008) evaluated the survival of probiotic strains of Lactobacillus casei Shirota and Bifidobacterium animalis subsp. lactis in a milk-based dessert with cranberry sauce.…”
Section: Similarly Ozcan Et Al (2010) Examined the Viability Of Lacmentioning
confidence: 99%
“…Survival of Lb. casei Shirota was previously investigated in different products such as a milk-based dessert containing cranberry sauce (Magarinos et al 2008) and ice cream (Sagdıç et al 2012). However, boza has not been evaluated as a probiotic carrier food for Lb.…”
mentioning
confidence: 99%